The Dialectic of the Two Poles of Ahmad Dahlan-Hasyim Asy'ari's Thought: Responding to the Challenges of Contemporary Islamic Education - Khikmatun Khikmatun; Abdul Khobir (ANWARUL, 2025)
This study addresses the complex challenges confronting contemporary Islamic education in Indonesia, including a values crisis, social polarization, and rapid technological change, which collectively underscore the need to reconstruct its educational paradigm on robust philosophical foundations. The study aims to explore the educational philosophies of Ahmad Dahlan and Hasyim Asy'ari, analyze the dialectic between modernity and traditionalism embedded in their epistemological frameworks, and evaluate the relevance of this dialectic for advancing contemporary Islamic education. Employing a library research methodology, the study conducts a comparative–reflective analysis of primary sources, such as Ahmad Dahlan’s speeches and treatises and Hasyim Asy'ari’s Adab al-'Alim wa al-Muta'allim—together with pertinent secondary literature. The findings reveal that Ahmad Dahlan’s thought prioritizes the integration of scientific knowledge, rational inquiry, and curriculum reform, whereas Hasyim Asy'ari emphasizes ethics, spirituality, and the preservation of tradition grounded in the principle of al-muhafadzah. Despite these differing emphases, their philosophies converge on the goal of cultivating individuals who are faithful, knowledgeable, and practically engaged in social transformation. The study concludes that the dialectic between their views constitutes not a binary opposition but a productive epistemological synthesis that fosters an integrative, moderate, and transformative model of Islamic education. This synthesis provides a philosophical foundation for reconstructing an educational paradigm that balances ethical–spiritual depth with the critical and creative competencies required to navigate the digital and pluralistic challenges of the twenty-first century.